2016
DOI: 10.1089/neu.2014.3846
|View full text |Cite
|
Sign up to set email alerts
|

Coated-Platelet Levels Increase with Number of Injuries in Patients with Mild Traumatic Brain Injury

Abstract: Coated-platelets are procoagulant platelets that are elevated in stroke and are associated with stroke recurrence. In a previous study, prompted by data showing an increased risk for stroke following traumatic brain injury (TBI), we found that coated-platelet levels are elevated in patients with combat-related mild TBI (mTBI) several years after the injury, compared with controls. We now investigate in an expanded patient population whether parameters commonly recorded in mTBI are related to increased coated-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Furthermore, while numerous cytokines have been found elevated for up to three months after severe TBI [ 79 ], few studies have evaluated the chronic inflammatory response after concussion. Yet, Prodan and colleagues found platelet activation in previously concussed military personnel ranging from 6 months to 9 years post-injury [ 33 ], and in a follow-up study, identified a positive correlation between this inflammatory correlate and the number of concussions sustained [ 80 ]. While these previous works evaluated military personnel and included mechanistically distinct blast-related concussion, the results are consistent with our findings, and suggest that biological perturbations resulting from multiple head injuries are evident systemically up to years after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while numerous cytokines have been found elevated for up to three months after severe TBI [ 79 ], few studies have evaluated the chronic inflammatory response after concussion. Yet, Prodan and colleagues found platelet activation in previously concussed military personnel ranging from 6 months to 9 years post-injury [ 33 ], and in a follow-up study, identified a positive correlation between this inflammatory correlate and the number of concussions sustained [ 80 ]. While these previous works evaluated military personnel and included mechanistically distinct blast-related concussion, the results are consistent with our findings, and suggest that biological perturbations resulting from multiple head injuries are evident systemically up to years after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets from TBI patients and those from rats and pigs subjected to experimental TBI have moderately low counts, are often activated, produce MVs, and express procoagulant activity. [55][56][57] Pulmonary and cerebral microthrombosis is also reported in animal models of TBI. 58 The cerebral microthrombi are mostly detected in the pericontusion cortex 59,60 and contain not only fibrin 61 but also platelets 58,60 and von Willebrand factor.…”
Section: Plateletsmentioning
confidence: 97%
“…Intriguingly, such findings only apply to subsets of the total platelet population; nevertheless, an increased presence of procoagulant cells can tip the balance from hemostasis to thrombosis. PS-expressing platelets that retain procoagulant and serotonin-derived adhesive proteins are often referred to as "coated" platelets; their levels are often increased after trauma, for example after brain injury and they have been implicated in stroke (78).…”
Section: Thrombin Generation and Microparticle Releasementioning
confidence: 99%